Protection of Brass in HCl Solution by L-Cysteine and Cationic Surfactant - Milan B. Radovanovic; Zaklina Z. Tasic; Marija B. Petrovic Mihajlovic; Milan M. Antonijevic (Advances in Materials Science and Engineering)
Electrochemical behavior of brass and inhibitory effect of L-cysteine in HCl solution are investigated using electrochemical techniques in addition to SEM-EDS analysis. Results show that inhibition efficiency depends on inhibitor concentration and immersion time of brass electrode in inhibitor solution. Electrochemical test results point to formation of Cu(I)-cysteine complex on the brass surface in chloride solutions with addition of different amounts of cysteine. The formed complex has an important role in inhibition of the corrosion process in the examined media because Cu(I)-cysteine significantly reduces dissolution of brass. Curves obtained in acidic solution in the presence of cysteine after pretreatment in sodium dodecyl sulfate (SDS) by cyclic measurements and potentiodynamic polarization measurements indicate intense inhibition of corrosion processes. Efficient inhibition of brass dissolution is result of formation of a stable protective layer on the brass surface after pretreatment of the electrode in SDS solution. The brass surface is modified in sodium dodecyl sulfate solution in order to increase cysteine adsorption on the electrode surface and to improve inhibition efficiency. Inhibition mechanism of cysteine includes adsorption on active sites on the electrode surface, which is confirmed by SEM-EDS analysis of brass. Adsorption of cysteine in hydrochloric acid solution obeys the Langmuir adsorption isotherm. Also, Gibbs free energy of adsorption has a value of −31.5 kJ/mol and indicates strong adsorption of cysteine on the electrode surface.